Case report: A colorectal cancer patient with microsatellite instability-high and MSH2 germline mutation failed to respond to anti-PD-1 immunotherapy - Zhang, Qun; Hu, Jing; Zhang, Yaping; Li, Li; Wang, Ting; Qian, Xiaoping (Frontiers in Immunology, 2022)
Lynch syndrome (LS) is characterized by germline mutations in the DNA mismatch repair (MMR) genes. In colorectal cancer (CRC), germline mutations of DNA MMR genes commonly lead to microsatellite instability-high (MSI-H) subtype formation. Recent studies have demonstrated that CRC patients with MSI-H or mismatch repair-deficient (dMMR) status can benefit from anti-PD1 immunotherapy. However, almost 50% of CRC patients with MSI-H status do not respond to it. It is reported that heterogeneity of tumor and abnormal activation of cancer-related signaling pathways contribute to resistance to anti-PD1 therapy. To improve the clinical efficacy of such patients, the underlying mechanisms of resistance to anti-PD1 treatment must be explored. In this case, we describe an LS-associated CRC patient with MSI-H who suffered resistance to anti-PD1 therapy. Here, we attempted to elucidate the potential reasons, and thus appropriate strategies may be derived to overcome this clinical problem.